Immunogenicity of an investigational hepatitis B vaccine with a toll-like receptor 9 agonist adjuvant (HBsAg-1018) compared with a licensed hepatitis B vaccine in subpopulations of healthy adults 18–70 years of age. Issue 31 (17th July 2015) - Janssen, Julia M.; Jackson, Sam; Heyward, William L.; Janssen, Robert S.
Highlights Phase 3 trial data of an investigational hepatitis B vaccine in subpopulations. HBsAg-1018 induced higher seroprotection rates than HBsAg-Eng. HBsAg-1018 demonstrated better consistency of SPRs in subpopulations than HBsAg-Eng.